Short communication. First deteccion of a phytoplasma infecting faba bean (Vicia faba L.) in Spain - Castro, S.=700 1 Romero, J.
(Es, En)
ilus., 18 ref.
Keywords: VICIA FABA; LEGUMINOSAS; ENFERMEDADES DE LAS PLANTAS; PCR; DNA; ESPAÑA; GRUPO DEL FITOPLASMA DE LA ENFERMEDAD; ANALISIS FILOGENETICO